Gestation in a Mare with Facial Deviation (Wry Nose) - Mousquer, Mariana Andrade; Müller, Vitória; Pazinato, Fernanda Maria; Suñe Moraes, Bruna dos Santos; Rafael, Leandro Américo; Curcio, Bruna da Rosa; Wayne Nogueira, Carlos Eduardo (Acta Scientiae Veterinariae, 2019)
Background: Wry nose is a congenital deformity that causes respiratory obstruction and decreased oxygenation rate. Gestation in a wry nose mare may be considered a risk to the neonate since it depends on the maternal environment for development. Compromised oxygenation during pregnancy can lead to fetal distress and cause consequences on fetal development. However, depending on the degree of the impairment, the fetus may still be able to adapt. The aim of the present study was to report the gestation in a mare with facial deviation until term and to assess blood gases in the mare and neonate, and to evaluate the histomorphometry of the placenta. Case: A Criollo breed mare presenting facial deviation (Wry Nose) was donated to Equine Medicine Research Group (ClinEq) of the Federal University of Pelotas (UFPel) due to the presence of the physical deformity. When the mare was five years old, it was inseminated and had a pregnancy confirmed. At the fifth month of gestation, evaluation of fetal aorta diameter, fetal orbital diameter and combined thickness of the uterus and placenta (CTUP) started to be performed monthly to assess gestation health. The assessment of the fetal orbit and aorta diameter revealed a linear increase of both variables with the progress of gestation indicating a normal fetal development. CTUP remained in the normal reference range, presenting no alterations during the gestational length. The mare foaled at 324 days of gestation a coat showing no congenital deformities. The foaling was monitored until the complete passage of fetal membranes. A complete clinical and hematological evaluation of the foal was carried out after birth. The foal showed normal adaptive behavior, clinical and hematological parameters during the first hours of life, although presenting physical signs of immaturity. Venous blood samples were collected from the mare at 315 days of gestation, immediately after foaling and 24 h post-partum for lactate and blood gas analysis. Mild changes were observed in the mare’s blood gas analysis at foaling that were compensated within 24 h post-partum. Venous blood samples were collected from the umbilical cord and from the foal after birth, at 12 and 24 h post-partum to measure blood gases and lactate. The newborn foal presented respiratory acidosis immediately after birth, which was metabolically compensated at 24 h post-partum. Both mare’s and foal’s lactate evaluation were within the normal reference ranges. After expulsion of the placenta, samples from the gravid horn, uterine body and non-gravid horn were collected for histological and histomorphometric evaluation. In the histological evaluation, avillous areas were detected in the gravid horn and uterine body and mild hypoplasia was found in the uterine body. Placental histomorphometry revealed larger total microcotiledonary and capillary areas on the non-gravid horn when compared to the remaining areas of the placenta (gravid horn and uterine body). No abnormalities on the placental vasculature were detected. Discussion: To date, there are no reports of a pregnancy in a mare with facial deviation in the literature. This report showed that the wry nose mare gave birth to a viable foal showing no congenital abnormalities, which suggests that wry nose animals can be bred normally. The mare presented a healthy pregnancy, with mild changes in the blood gas analysis at foaling that were compensated at 24 h postpartum. Similarly, despite the foal showed physical signs of immaturity and respiratory acidosis at birth, these changes were compensated in the later assessments. Furthermore, no abnormalities on the placental vasculature were detected.